2022
DOI: 10.1186/s12986-022-00643-x
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal status, age at natural menopause and risk of diabetes in China: a 10-year prospective study of 300,000 women

Abstract: Background Menopause characteristics have been implicated in future health consequences, yet little is known about its relevance to diabetes. We examined the associations of menopausal status and age at natural menopause with diabetes risk in Chinese women. Methods We used prospective data of the China Kadoorie Biobank study that recruited 302,522 women aged 30–79 years in 2004–2008 from 10 areas across China. During average 10.8 years of follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…In addition, sex differences in glucose homeostasis have been observed in human and rodent models, suggesting that there is a potentially protective role of female sex hormones in preventing diabetes [ 43 ]. A large cohort study in China involving 300,000 people found that perimenopausal and postmenopausal women had an increased risk of developing diabetes compared to premenopausal women, with HRs of 1.17 (95% CI: 1.06–1.29) and 1.15 (1.06–1.25) [ 44 ]. Estradiol has been shown in animal experiments to increase insulin content and glucose-stimulated insulin secretion in mouse islets, suggesting that this hormone plays an active role in glucose homeostasis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sex differences in glucose homeostasis have been observed in human and rodent models, suggesting that there is a potentially protective role of female sex hormones in preventing diabetes [ 43 ]. A large cohort study in China involving 300,000 people found that perimenopausal and postmenopausal women had an increased risk of developing diabetes compared to premenopausal women, with HRs of 1.17 (95% CI: 1.06–1.29) and 1.15 (1.06–1.25) [ 44 ]. Estradiol has been shown in animal experiments to increase insulin content and glucose-stimulated insulin secretion in mouse islets, suggesting that this hormone plays an active role in glucose homeostasis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aggravating factors include chronic inflammation due to poor hygiene, eczema, seborrheic dermatitis, lichen planus or sclerosis, local trauma, and recurrent urinary tract infections (4)(5)(6). In this case, the patient's age at menopause was 47, earlier than the average age of menopause (7). After menopause, she had not received hormone replacement therapy and was in a long-term low oestrogen state.…”
Section: Discussionmentioning
confidence: 86%
“…The age of the patient is a risk factor for ovarian hypofunction. In Chinese females, the average age of menopause is 48.2 years [4]. However, the high FSH and LH levels were not related to age, since she returned to normal FSH and LH levels and regular menstrual soon after quitting dulaglutide.…”
Section: Discussionmentioning
confidence: 93%